ANALYSIS OF THE IMPACT OF TRAINING AND DEVELOPMENT, JOB SATISFACTION, AND ORGANISATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE - Kosasih Kosasih; Nia Widyawati Nur; Ary Kafin Kosasih; Alexandre de Sousa Guterres (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to describe training and development, job satisfaction, and organisational commitment to employee performance. Employee performance is a crucial factor that determines the success of an organisation. Therefore, understanding the factors that influence it is important in human resource management. The method used in this research is a literature review, by collecting and reviewing various relevant literature, scientific journals, and previous research results. The results of the study show that employee training and development contribute significantly to improving work ability and effectiveness. Meanwhile, job satisfaction affects employee motivation, loyalty and morale. On the other hand, organisational commitment strengthens employees' psychological attachment to the place where they work, thus encouraging optimal performance. In conclusion, the three variables are interrelated and together make an important contribution to improving employee performance. Organisations need to establish an integrated human resource strategy to maximise the potential of employees as the company's main asset.